Transition to high school: Policy management of flow correction and educational trajectories - Lima, Maria de Fatima Magalhaes de; Paes de Carvalho, Cynthia (Education Policy Analysis Archives, 2021)
This study analyzes the possible relations between a student flow correction policy in a public education system and the transition to high school. The study of students' educational trajectories was the resource used to understand the results of the policy management and its possible effects on middle school transitions to high school. The analysis used data from the School Census, the education system's enrollment base, and available official documents on the policy and its management. Initially, the context of the policy design and management - structured within a public/private partnership - and the educational trajectories of the entire population of students enrolled in the system studied in the fifth grade in 2010 are presented. Subsequently, the trajectories of those who reached high school in 2014 are presented. The results suggest that, although the correction of student’s flow has favored entry into high school through projects of learning acceleration, the high repetition rate in the following year – the first year of the new stage of schooling - shows that access to high school may not correspond to a sustainable and well consolidated learning process, highlighting the limits of the controversial compensatory nature of the policy on screen.